2012
DOI: 10.1016/j.coph.2012.01.016
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK inhibitors, IKK2 inhibitors, and TNFα inhibitors in COPD

Abstract: COPD represents a major respiratory disorder, causing significant morbidity and mortality throughout the world. While therapies exist for COPD, they are not always effective, and many patients experience exacerbations and morbidity despite current therapies. Study of the molecular mechanisms involved in the underlying physiological manifestations of COPD has yielded multiple new targets for therapeutic intervention. In this review, we discuss signaling pathways involved in COPD pathogenesis and review clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 48 publications
0
25
0
2
Order By: Relevance
“…32, 33 In the pathogenic processes of COPD, p38 MAPK signaling has been found to have roles in the activation of inflammation cascade and infiltration of immunocytes in vivo and in vitro . 34 One clinical trial demonstrated a better clinical efficacy in COPD patients receiving p38 MAPK inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…32, 33 In the pathogenic processes of COPD, p38 MAPK signaling has been found to have roles in the activation of inflammation cascade and infiltration of immunocytes in vivo and in vitro . 34 One clinical trial demonstrated a better clinical efficacy in COPD patients receiving p38 MAPK inhibitor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…p38 MAPK inhibitors therefore seem a promising new line of treatment. Currently, several clinical trials explore the feasibility of this approach [82].…”
Section: P38 Mapkmentioning
confidence: 99%
“…Indeed, there is ongoing clinical development of MAPK14 inhibitors to block inflammation in COPD and asthma (61,62). In either case, the present identification and validation of the CLCA1 to MAPK13 signaling pathway to excess mucus production offers an opportunity to better define the regulation of a major disease end point and to respond to the unmet need for an anti-mucus therapeutic for inflammatory airway disease.…”
Section: Figurementioning
confidence: 99%